1979
DOI: 10.1161/01.str.10.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The disability oriented rehabilitation unit--a major factor influencing stroke outcome.

Abstract: SUMMARY Many investigators have analyzed the effectiveness of the cardiac care unit (as a model of a disability oriented, specially staffed, geographically isolated unit) in altering outcome following acute myocardial infarction. Little data are available, however, on the efficacy of caring for patients with stroke on specially staffed disability oriented units. Of 667 patients with stroke recently discharged from the Burke Rehabilitation Center, 589 were admitted to the stroke unit (SU group) and 78 were admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

1979
1979
1994
1994

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 14 publications
0
12
2
Order By: Relevance
“…The first such study 9 reported no benefit for mildly and severely affected patients but a significantly better outcome for patients with moderate disabilities. Feigenson and colleagues 10 showed in a similar trial that patients admitted to a stroke unit were more likely to be discharged home and were able to walk better.…”
Section: Evidence Concerning the Effectiveness Of Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The first such study 9 reported no benefit for mildly and severely affected patients but a significantly better outcome for patients with moderate disabilities. Feigenson and colleagues 10 showed in a similar trial that patients admitted to a stroke unit were more likely to be discharged home and were able to walk better.…”
Section: Evidence Concerning the Effectiveness Of Rehabilitationmentioning
confidence: 99%
“…10 Moreover, selection criteria for patient admittance are not uniform, and duration, type, and onset of rehabilitation differ. Finally, measurements of outcome are not constant.…”
Section: Evidence Concerning the Effectiveness Of Rehabilitationmentioning
confidence: 99%
“…Feigensen, Gitlow and Greenberg compared 589 patients treated in a disability-orientated stroke unit with only 78 patients admitted to other units of the same rehabilitation centre. 25 Both groups had similar treatment programmes provided by staff who had rotated through the Stroke Unit. They concluded that even in a rehabilitation centre specialising in treating functional disabilities, patients with stroke are more likely to improve if placed in a disability-orientated unit than if they are admitted to mixed disability units which are scattered throughout the hospital.…”
Section: Stroke Rehabilitation Units/corrairavmentioning
confidence: 99%
“…The data showed that although the SU group had more concurrent medical problems and more severe neurological and functional deficits, they were more likely to go home after treatment and walked better at the time of discharge. 20 LOS was similar for both groups. Substantial improvement in outcome thus may be realized by regionalizing care into disability-oriented units, not only in acute care hospitals, but also in rehabilitation facilities.…”
Section: Stroke Vol 10 No 1 January-february 1979mentioning
confidence: 78%